Pengaruh Pemasaran Kewirausahaan dan Citra Merek terhadap Keunggulan Bersaing Batik Rindani di Kota Jambi - Indah Putri E; Dahmiri Dahmiri; Sigit Indrawijaya (Journal of Management and Creative Business, 2024)
This research aims to determine the influence of entrepreneurial marketing and brand image on the competitive advantage of batik rindani in the city of Jambi. The population in this study is consumers of Batik Rindani in the city of Jambi, with a sample size calculated based on the Hair formula, totaling 80 respondents. The data collection technique used is a questionnaire in the form of a Google Form. The sampling technique used is nonprobability sampling, specifically purposive sampling. Data analysis methods used are descriptive method and quantitative method, specifically multiple linear regression analysis using SPSS version 26. The results of this study indicate that (1) entrepreneurial marketing and brand image have a positive and significant effect on the competitive advantage of Batik Rindani in the city of Jambi. (2) Brand image has the most dominant influence on the competitive advantage of Batik Rindani in the city of Jambi.